AB1002 Do Foot Posture and the Age-Related Variations Led to Sonographic Abnormalities in the Paediatric Healthy Foot?. (10th June 2014) - Collado, P.; Gonzalez, M.L.; Alcalde, M.
Abstract : Background: As ultrasonography has proven to be a helpfulness tool for detecting articular and periarticular foot disease in juvenile idiopathic arthritis, the interpretation of some findings such as effusion or power Doppler signal in children throughout the skeleton and walking developments might be problematic. Objectives: To describe the normal sonoanatomy of the foot joints in a cohort of healthy children and examine its association to foot posture, providing references for the assessment of inflammatory joint pathologies during the growth period. Methods: Using a multiplanar, dynamic technique, 55 healthy children (34 boys and 21 girls; age range, 9 months to 15 years) were examined by high-frequency gray-scale and power Doppler ultrasonography (110 foot, including 8 joints, 8 tendons and 3 periarticular soft tissues) (table 1). The sites were examined for synovial hypertrophy, effusion, tenosynovitis, abnormal tendon insertion echogenecity, or power Doppler signal. A dichotomous scoring system was employed to determine each site examined as sonographic normal appearance (absence or presence of the above mentioned findings). Foot posture was categorized as normal, pronated, or supinated using the Foot Posture Index (1). Results: Distension of the dorsal recess in the first metatarsophalangeal (1st MTP) joint because of the presence of small effusion was detected in 24/55 feet (43.6%) and 21/55 feet (38.2%) in the right and left side, respectively. Ultrasonography showed power Doppler signal within the tibiotalar joint capsule (36% of the 110 feet) (figure 1), in the Achilles tendon area (19%), and, less frequently, in the epiphyseal cartilage of the some tarsal bones (figure 2). None of the examined feet showed synovial hypertrophy, tenosynovitis or abnormalities in tendon insertion. Normal foot posture was found to be more frequent (61%). Foot posture was not significantly associated with sonographic abnormal appearance. Conclusions: Distension of the dorsal recess in the 1st MTP joint recess is a common and normal finding detected in childhood. Tibiotalar intra-capsular PD signal and epiphyseal cartilage signal in the navicular and calcaneus may also be visualized as normal findings in healthy children. Those findings are relevant for interpreting sonographic findings in children with inflammatory diseases. Unlike adults, foot posture seems not to be associated with the presence of abnormal appearance in children (2). References: Redmond AC, Crosbie J, Ouvrier RA. Development and validation of a novel rating system for scoring standing foot posture: the Foot Posture Index. Clin Biomech 2006; 21: 89–98 Menz HB, Dufour AB, Riskowski JL, Hillstrom HJ, Hannan M. Association of planus foot posture and pronated foot function with foot pain: The Framingham Foot Study. Arthritis Care Res 2013; 65:1991–1999 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4702